NORMATIVE STRENGTH OF GREEN BELT AND ROAD INITIATIVE ENVIRONMENTAL STANDARDS BETWEEN VOLUNTARY AND BINDING - Muhammad Zaki daniswara; Gonda Yumitro (Universitas Budi Luhur, 2026)
Abstract: The Belt and Road Initiative (BRI) is one of the world's largest infrastructure development projects with a major influence on environmental management at the international level. China introduced the Green Belt and Road Initiative (Green BRI) as a step to encourage more environmentally friendly development and reduce the impact of climate change. However, debate continues regarding the effectiveness of the environmental standards used, particularly concerning whether these standards are voluntary or mandatory. This research aims to analyze the characteristics of environmental standards applied within the Green BRI and to evaluate the extent to which a soft-law-based governance model can help encourage adherence to the global sustainable development agenda. The method used is descriptive qualitative with a literature study approach, analyzing policy documents, academic articles, and institutional reports produced during the 2019 to 2025 period. The research shows that environmental standards within the Green BRI are still dominated by characteristics of flexible regulation, marked by a lack of clear legal obligations, ambiguity in implementation indicators, and the absence of strong enforcement and sanction mechanisms. The ability to implement these standards depends on the regulatory capacity of the recipient country, domestic economic interests, and the role of non-state actors. These findings indicate that legal instruments lacking binding force (soft law) are less able to create sustainable environmental compliance. Abstrak: Belt and Road Initiative (BRI) adalah salah satu proyek pembangunan infrastruktur dunia terbesar yang memiliki pengaruh besar terhadap pengelolaan lingkungan di tingkat internasional. Tiongkok mengenalkan Green Belt and Road Initiative (Green BRI) sebagai langkah untuk mendorong pembangunan yang lebih ramah lingkungan dan mengurangi dampak perubahan iklim.Namun, masih terjadi perdebatan mengenai efektivitas standar lingkungan yang digunakan, khususnya terkait apakah standar tersebut bersifat sukarela atau wajib. Penelitian ini bertujuan untuk menganalisis karakteristik standar lingkungan yang berlaku dalam Green BRI serta mengevaluasi sejauh mana model tata kelola yang berlandaskan soft law bisa membantu mendorong pengikutan terhadap agenda pembangunan berkelanjutan secara global. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan studi pustaka, yaitu dengan menganalisis dokumen kebijakan, artikel akademik, dan laporan institusional yang dibuat selama periode 2019 hingga 2025. Penelitian menunjukkan bahwa standar lingkungan dalam Green BRI masih didominasi oleh ciri-ciri undang-undang yang bersifat fleksibel, yang ditandai dengan kurangnya kewajiban hukum yang jelas, ketidakjelasan dalam indikator penerapan, serta tidak adanya mekanisme pengawasan dan sanksi yang berlaku secara kuat. Kemampuan penerapan standar itu bergantung pada kemampuan pengaturan negara tujuan, kepentingan ekonomi dalam negeri, serta peran aktor yang bukan pemerintah. Temuan ini menunjukkan bahwa aturan perundang-undangan yang tidak memiliki kekuatan hukum (soft law) kurang mampu menciptakan kepatuhan lingkungan yang berkelanjutan.